PEMANFAATAN KONSORSIUM BAKTERI LOKAL UNTUK BIOREMEDIASI LIMBAH TEKSTIL MENGGUNAKAN SISTEM KOMBINASI ANAEROBIK-AEROBIK - I Dewa K Sastrawidana; Bibiana W Lay; Anas Miftah Fauzi; Dwi Andreas Santosa (BERITA BIOLOGI, 2008)
The objective of this research is to study the potential use microorganisms which are identified as Aeromonas sp., Pseudomonas $p., Flavobaclerium sp., Plesiomonas sp. and Vibrio sp. Five bacteria strains from sludge of Badung river were identified as Vibrio sp. and Plesiomonas sp. Two anaerobic-aerobic reactors were operated to treat textile waste water. Each reactor contained vulcanic stone to increase spesific surface of media for attachment of bacteria.Bacteria consortia used for anaerobic process consist of Aeromonas sp. (ML6), Aeromonas sp. (ML14), Aeromonas sp. 9ML24), Pseudomonas sp. (ML8) and Flavobacterium sp. (ML20). Whereas, bacteria consortia for aerobic process consist of Plesiomonas sp. (SB1), Plesiomonas sp. (SB2), Vibrio sp.(SB1), Vibrio sp. (SB2) and Vibrio sp. (SB3). The system was operated for 3 day in each reactor. The result showed, biodegradation of textile waste water in combined anaerobic-aerobic system by attached growth process is potential for treatment of textile waste water.This technology is effective to decrease COD value up to 98.38%, BODS 93.90%, TDS 80.87%, TSS 87.50% and decolorization of textile dyes up to 95.57%.